If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 41 + -8x + -9 = -6x + -9 + -23 Reorder the terms: 41 + -9 + -8x = -6x + -9 + -23 Combine like terms: 41 + -9 = 32 32 + -8x = -6x + -9 + -23 Reorder the terms: 32 + -8x = -9 + -23 + -6x Combine like terms: -9 + -23 = -32 32 + -8x = -32 + -6x Solving 32 + -8x = -32 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 32 + -8x + 6x = -32 + -6x + 6x Combine like terms: -8x + 6x = -2x 32 + -2x = -32 + -6x + 6x Combine like terms: -6x + 6x = 0 32 + -2x = -32 + 0 32 + -2x = -32 Add '-32' to each side of the equation. 32 + -32 + -2x = -32 + -32 Combine like terms: 32 + -32 = 0 0 + -2x = -32 + -32 -2x = -32 + -32 Combine like terms: -32 + -32 = -64 -2x = -64 Divide each side by '-2'. x = 32 Simplifying x = 32
| 1*9= | | ln(x-7)-ln(x+2)=ln(x-4)-ln(x+2) | | s-(-4s+2)=13 | | 10-4(l+7)=2(1-L) | | 2[3+2x+9]=28x+132 | | x^2+4x=15 | | l=10-2w | | 2x^2-7x+25=0 | | -7x+9=x+1 | | 18+w/8=74 | | 64t=12t^2+45 | | 7x-2(4x-6)= | | 22d-(6+2d)=4 | | x=6y+4 | | 10+4n-4=5n-7 | | 16x^2=4x^2+3x+1 | | x-25=-7 | | 60c-54(c-2)=0 | | (x-4)(x+7)(x+1)=0 | | a^2+9=6a | | 14x^3-68x^2-10x=0 | | 8m^3-12m^2-8m= | | 4(3x+12)=5x-1 | | q=mw-mw^2 | | x^3+3x^2+5x+15=0 | | x^2+13x+9=0 | | 0.5x^2+0.6x=0 | | 12-7=5x+49 | | 12-11w+2w^2=0 | | -4x^2+32x-64=0 | | 48p^2-675=0 | | 7(b-3)=8b+2 |